Analysis of the Number of Pregnant Women Suffering from Chronic Energy Deficiency (CED) in Palu City: 2023-2024 - Devi Savitri Effendy; Evi Fitriani; Wiwid Arsanda (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2026)
Background: Chronic Energy Deficiency (CED) among pregnant women remains a significant public health concern due to its adverse effects on both maternal and fetal health. In Indonesia, the prevalence of CED among pregnant women remains relatively high, particularly in areas with limited access to healthcare services. Objective: This study aimed to describe the distribution of Chronic Energy Deficiency (CED) among pregnant women in Palu City during the 2023–2024 period based on secondary data obtained from the Central Bureau of Statistics (BPS) of Palu City. Methods: This study employed a quantitative descriptive design using secondary data obtained from the Central Bureau of Statistics of Central Sulawesi Province. The data analyzed included the number of pregnant women affected by Chronic Energy Deficiency. Data were presented graphically and analyzed descriptively to identify patterns and trends, which were subsequently interpreted narratively. Results: The findings revealed fluctuations in the number of pregnant women with Chronic Energy Deficiency between 2023 and 2024. Overall, a decrease in the number of CED cases was observed during the study period. Geographical conditions, limited healthcare facilities, and socio-cultural factors were identified as potential contributors to the observed trends. Conclusion: Chronic Energy Deficiency before and during pregnancy can increase the risk of adverse birth outcomes, particularly low birth weight. Although annual variations were observed, the persistent occurrence of CED among pregnant women highlights the urgent need for sustainable interventions, especially in areas with limited access to healthcare services. Keywords: Pregnant Women; Chronic Energy Deficiency; Malnutrition; Low Birth Weight; Healthcare Accessibility; Indonesia.